Microfluidics combined with fluorescence in situ hybridization (FISH) for Candida spp. detection - Barbosa, Violina Baranauskaite; Rodrigues, Célia F.; Cerqueira, Laura; Miranda, João M.; Azevedo, Nuno F. (Frontiers in Bioengineering and Biotechnology, 2022)
One of the most prevalent healthcare-associated infection is the urinary tract infection (UTI), caused by opportunistic pathogens such as Candida albicans or non-albicans Candida species (NACS). Urine culture methods are routinely used for UTI diagnostics due to their specificity, sensitivity and low-cost. However, these methods are also laborious, time- and reagent-consuming. Therefore, diagnostic methods relying on nucleic acids have been suggested as alternatives. Nucleic acid-based methods can provide results within 24 hours and can be adapted to point-of-care (POC) detection. Here, we propose to combine fluorescence in situ hybridization (FISH) with a microfluidic platform for the detection of Candida spp.. As a case study we used C. tropicalis, which is reported as the second most common NACS urine isolate obtained from patients suspected with UTI. The microfluidic platform proposed in this study relies on hydrodynamic trapping, and uses physical barriers (e.g., microposts) for the separation of target cells from the suspension. Using a specific peptide nucleic acid (PNA) probe, the FISH procedure was applied onto previously trapped C. tropicalis cells present inside the microfluidic platform. Fluorescence signal intensity of hybridized cells was captured directly under the epifluorescence microscope. Overall, the PNA probe successfully detected C. tropicalis in pure culture and artificial urine (AU) using FISH combined with the microfluidic platform. Our findings reveal that FISH using nucleic acid mimics (PNA) in combination with microfluidics is a reliable method for the detection of microorganisms such as C. tropicalis. As such, this work provides the basis for the development of a POC detection platform in the future.